13-Valent vaccine serotype pneumococcal community acquired pneumonia in adults in high clinical risk groups. Issue 12 (14th March 2018) - Daniel, Priya; Rodrigo, Chamira; Bewick, Thomas; Sheppard, Carmen; Greenwood, Sonia; McKeever, Tricia M.; Trotter, Caroline; Lim, Wei Shen
Abstract: There is debate regarding the value of vaccinating adults with the 13-valent pneumococcal conjugate vaccine (PCV-13). This analysis was conducted to investigate the risk of PCV-13 serotype community acquired pneumonia (CAP) in hospitalised adults with co-morbid disease and risk factors for pneumococcal disease in the UK. Consecutive adults hospitalised (2008–2013) with a primary diagnosis of CAP, were recruited. Pneumococcal aetiology disease was identified by use of pneumococcal urinary antigen detection and serotype identification using a validated multiplex immunoassay or serum latex agglutination. Adults with PCV-13 serotype CAP were compared to those with non-PCV-13 serotype CAP. Of 2224 patients, PCV-13 serotype CAP was identified in 337 (15.2%) and non-PCV-13 serotype CAP in 250 (11.2%) individuals. Adults aged ≥65 years with one or more clinical risk factors had a significantly lower risk of PCV-13 serotype CAP compared to those aged 16–64 years without clinical risk factors (aOR 0.61, 95%CI 0.41–0.92, p = .018). In a stacked-risk analysis, the presence of incremental clinical risk factors was associated with lower odds of PCV-13 disease (p for trend = .029) Adults with underlying chronic respiratory disease (aOR) 0.56, 95% CI 0.36–0.85, p = .007) and chronic kidney disease (aOR 0.48, 95% CI 0.25–0.92, p = .028) had significantly lower adjusted odds of PCV-13 compared to non-PCV-13 serotype CAP. This analysis suggests that in the UK, the burden of PCV13 disease is greater in adults outside the traditional 'at-risk' groups compared to adults in 'at-risk' groups.